Essential Islam : a comprehensive guide to belief and practice - Morgan, Diane, 1947- (Praeger/ABC-CLIO, 2010)
Essential Islam: A Comprehensive Guide to Belief and Practice is the ideal beginner's resource on the core elements of a faith that, like Christianity and Judaism, offers a guide to holy living and a path to salvation--one that like other world faiths has inspired peace and war, tolerance and brutality, enlightenment and abysmal ignorance. Essential Islam offers an insightful, objective look at Islam from its inception to the present day, including a discussion of Islamic beliefs about God, history, warfare, marriage, the afterlife, and the relationship between Islam and other faiths. It is a rich source for dispelling misconceptions--for example, only 10 percent of Muslims are Arabic, and only a quarter of those reside in the Middle East--and for understanding tensions between groups within and outside Islam. More importantly, it gives readers a portrait of Islam not as a religion of extremists, but as a dynamic living faith practiced by people of all kinds in virtually every corner of the world.